Endobronchial Perfluorane Therapy for Aspiration Damages to the Tracheobronchial Tree: Clinical Experience - V. P. Vvedensky; A. V. Zabusov; P. S. Zhbannikov; P. A. Lyuboshevsky (Общая реаниматология, 2005)
The outcomes of treatment of aspiration damages to the tracheobronchial tree, by performing the goal-oriented endobronchial perfluorane treatment were analyzed in victims with severe brain injury. The specific features of the time course of pathological tracheal and bronchial mucosal changes were defined during the therapy performed. The determinants of the efficiency of endobronchial perfluorane therapy were determined in the treatment of tracheal and bronchial damages of aspiration genesis.